Au nanoparticle decorated graphene oxide as a novel coating for solid-phase microextraction1. Issue 52 (10th June 2015) - Xu, Lili; Suo, Hongbo; Liang, Xiaojing; Wang, Licheng; guo, Yong; Jiang, Shengxiang
<x xml:space="preserve">Abstract</x> A novel solid-phase microextraction (SPME) fiber based on a stainless steel wire coated with Au nanoparticle decorated graphene oxide was prepared using a novel protocol.